Mesoporous Silica Nanoparticles for the Treatment of Complex Bone Diseases: Bone Cancer, Bone Infection and Osteoporosis - Miguel Gisbert-Garzarán; Miguel Manzano; María Vallet-Regí (MDPI AG, 2020)
Bone diseases, such as bone cancer, bone infection and osteoporosis, constitute a major issue for modern societies as a consequence of their progressive ageing. Even though these pathologies can be currently treated in the clinic, some of those treatments present drawbacks that may lead to severe complications. For instance, chemotherapy lacks great tumor tissue selectivity, affecting healthy and diseased tissues. In addition, the inappropriate use of antimicrobials is leading to the appearance of drug-resistant bacteria and persistent biofilms, rendering current antibiotics useless. Furthermore, current antiosteoporotic treatments present many side effects as a consequence of their poor bioavailability and the need to use higher doses. In view of the existing evidence, the encapsulation and selective delivery to the diseased tissues of the different therapeutic compounds seem highly convenient. In this sense, silica-based mesoporous nanoparticles offer great loading capacity within their pores, the possibility of modifying the surface to target the particles to the malignant areas and great biocompatibility. This manuscript is intended to be a comprehensive review of the available literature on complex bone diseases treated with silica-based mesoporous nanoparticles—the further development of which and eventual translation into the clinic could bring significant benefits for our future society.